Respuesta :
The average rate of change (m) of function g(x) on interval [a, b] is given by
... m = (g(b) -g(a))/(b -a)
Here, we have
- g(3) = 723
- g(0) = -5
so the average rate of change is
... m = (723 -(-5))/(3 - 0) = 728/3 = 242 2/3
![Ver imagen sqdancefan](https://us-static.z-dn.net/files/db3/d80b72c03fdb13dcfbd5ad2e8944d67d.jpeg)
Answer:
The average rate of the function g(x)=6
Step-by-step explanation:
We are given that a function [tex]g(x)=3(2x)-6[/tex] on the interval [0,3]
We have to find the value of rate of change of the given function over the interval [0,3]
To find the value of average rate of change of the function we apply slope formula
Average rate=Slope=m=[tex]\frac{y_2-y_1}{x_2-x_1}[/tex]
Let a=0, b=3
Now, [tex]g(a)=3(2\cdot0)-6=-6[/tex]
g(b)=[tex]3(2\cdot3)-6=18-6=12[/tex]
Now, the average rate of the function g(x)=[tex]\frac{g(b)-g(a)}{b-a}[/tex]
Average rate of the function g(x)=[tex]\frac{12-(-6)}{3-0}[/tex]
Average rate of the function g(x)=[tex]\frac{18}{3}=6[/tex]
Hence, the average rate of the function g(x)=6
Answer :6